Development of an Instrument for Measuring Intention to ACT and Healthy Eating Behavior of Students - Harahap, Lia Junita; Harahap, Lena Juliana (Universitas Nahdlatul Ulama Surabaya, 2024)
The instrument is one of the supporting successes of learning. Assessment of student behavior will influence students' thoughts and decisions in taking more positive action. This study aims to develop a valid and reliable instrument for students' intention to act and Healthy Eating Behavior. The resulting instrument was a test in the form of a checklist. This research was conducted from March to April 2022 at SMA Negeri 1 Sayur Matinggi with a sample of 38 students from Natural Science 1 and Natural Science 2 classes. The research method uses the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) adopted from the Branch. However, this research only reached the development stage. The results showed that the instrument for assessing the intention to act, and Healthy Eating Behavior was feasible with the respective expert validation results of 87.50 and 84.38. The results of the empirical validation show that 41 questions about the intention to act and 40 questions about healthy eating behavior were valid because they were more than 0.320, and the reliability was more than 0.6.